2009
DOI: 10.18579/jpcrkc/2009/8/4/79677
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Evaluation of Chitosan Microcapsules Containing Rifampicin

Abstract: The present investigation was designed to prepare chitosan microcapsules and evaluate the in-vitro release pattern of the drug rifampicin. The microcapsules were formulated by glutaraldehyde cross-linking method using various core:coat ratios. The prepared microcapsules were evaluated for SEM analysis, sieve analysis, drug content, encapsulation efficiency, swelling studies, in-vitro and mucoadhesion test, and were compared with pure drug. The microcapsules obtained were spherical, discrete, free flowing and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0
2

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
0
2
0
2
Order By: Relevance
“…Recently, the possibilities of different drug delivery systems usage (DDS) for antituberculosis drugs has been studied more: polymeric composites, microparticles, nanoparticles, liposomes, the hollow and filled capsules [2][3][4][5][6][7][8][9][10][11][12]. As a model of antituberculosis drug rifampicin has been more studied [5][6][7][8][11][12].…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, the possibilities of different drug delivery systems usage (DDS) for antituberculosis drugs has been studied more: polymeric composites, microparticles, nanoparticles, liposomes, the hollow and filled capsules [2][3][4][5][6][7][8][9][10][11][12]. As a model of antituberculosis drug rifampicin has been more studied [5][6][7][8][11][12].…”
mentioning
confidence: 99%
“…The authors [11] have prepared the chitosan-alginate microcapsules containing antituberculosis drugs rifampicin, isoniazide or pyrazinamide in the ratio drug: alginate: chitosan 1:2:2. They have shown that drug release from microcapsules happens within 72 hours.…”
mentioning
confidence: 99%
See 2 more Smart Citations